2005
DOI: 10.1111/j.1365-2934.2005.00546.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors contributing to the decision to leave nursing care: a study among Swedish nursing personnel

Abstract: The fact that nursing personnel leave because of unsatisfactory salary and lack of professional opportunities underpins the importance of making nursing more attractive in terms of financial and professional development. However, the sample size of this study was relatively small and larger studies are thus required to further investigate the importance of these factors in the decision to leave nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 24 publications
8
78
0
3
Order By: Relevance
“…Blau and Kahn (2013), for example, find that women in the US face a relatively binary decision between full-time work and non-participation, while in other OECD countries the working hour flexibility produced by family-friendly policies results in substantially higher female participation rates than in the US, with more women working part-time. Fochsen et al (2005) find similar patterns within the Swedish nurse population, where the increased flexibility provided in work schedules since the mid-1990s has reduced exit from the profession for child rearing. Focusing on US women with a university qualification from Harvard, Herr and Wolfram (2012) find evidence that inflexible work environments lead to lower labour force participation once women have children.…”
Section: The Dynamics Of Labour Supplysupporting
confidence: 52%
“…Blau and Kahn (2013), for example, find that women in the US face a relatively binary decision between full-time work and non-participation, while in other OECD countries the working hour flexibility produced by family-friendly policies results in substantially higher female participation rates than in the US, with more women working part-time. Fochsen et al (2005) find similar patterns within the Swedish nurse population, where the increased flexibility provided in work schedules since the mid-1990s has reduced exit from the profession for child rearing. Focusing on US women with a university qualification from Harvard, Herr and Wolfram (2012) find evidence that inflexible work environments lead to lower labour force participation once women have children.…”
Section: The Dynamics Of Labour Supplysupporting
confidence: 52%
“…In a study among the European nurses, the three most important factors strongly associated with nurses' intention to leave were poor professional opportunities, unpleasant work organization, and low health status (38). Another study from Sweden found that an unsatisfactory salary contributed most to the nurse's decision to leave (39). One study on nurses in the UK suggested that work environment-related factors rather than individual or demographic factors were still of most importance to the turnover in nurses and their intention to leave (40).…”
Section: Discussionmentioning
confidence: 99%
“…Jellemző volt a mintánk tagjainak körében kifejezett elégedetlenség a szakma ál-tal nyújtottakkal szemben. A rossz tapasztalatokból fakadóan többen elhagynák az egészségügyi pályát, valamint ismerőseiknek, barátaiknak sem ajánlanák ezt a foglalkozást [21][22][23]. A megkérdezettek kétharmada eltérő mér-tékben ugyan, de elégedetlen jelenlegi élethelyzete valamely aspektusával.…”
Section: Táblázatunclassified